The Influence of Time Perspective on Cervical Cancer Screening among Latinas in the United States - Roncancio, Angelica M. (2013)
To develop effective interventions to increase cervical cancer screening among Latinas, we should understand the role of cultural factors, such as time perspective, in the decision to be screened. We examined the relation between present time orientation, future time orientation and self-reported cervical cancer screening among Latinas. A group of 206 Latinas completed a survey measuring factors associated with screening. Logistic regression analyses revealed that future time orientation was significantly associated with self-reported screening. Understanding the influence of time orientation on cervical cancer screening will assist us in developing interventions that effectively target time perspective and screening.